Criminal Records - Larrauri, Elena (EUNOMÍA. Revista en Cultura de la Legalidad, 2015)
Though the lack of specific studies it is a widespread assumption in Spain that having a criminal record may entail lowering the opportunities of employment and eventually affect other human rights. This article focuses on the effects that criminal background checks have for the right to privacy and social reintegration. It contrasts the North American view with the European on publicity, erasure of criminal records, and criminal background checks by employers.